Analysing the Expression of Eight Clock Genes in Five Tissues From Fasting and Fed Sows - Cardoso, Tainã Figueiredo; Quintanilla, Raquel; Castelló, Anna; Mármol-Sánchez, Emilio; Ballester, Maria; Jordana, Jordi; Amills, Marcel (Frontiers in Genetics, 2018)
In a previous study, we observed that circadian clock genes are differentially expressed in the skeletal muscle of fasting and fed sows. The goal of the current work was to investigate if these genes are also differentially expressed in tissues containing the central (hypothalamus) and peripheral (duodenum, dorsal fat, muscle, and liver) clocks. As animal material, we used 12 sows that fasted 12 h before slaughtering (T0) and 12 sows that were fed ad libitum 7 h. prior slaughtering (T2). Tissue samples were collected immediately after slaughter and total RNA was subsequently extracted. The expression of the ARNTL, BHLHE40, CRY2, NPAS2, NR1D1, PER1, PER2 and SIK1 genes was measured by quantitative reverse transcription PCR. The numbers of clock genes showing differential expression before and after feeding varied depending on the tissue i.e. four in dorsal fat and duodenum, six in skeletal muscle and seven in the liver. In contrast, none of the eight analysed genes displayed a significant differential expression in hypothalamus, the tissue where the central clock resides. This result supports that the differential expression of clock genes in the four tissues mentioned above is probably induced by nutrition and not by the central clock entrained by light. Moreover, we have observed that the NPAS2 and ARNTL genes display positive log2(FC) values in the five tissues under analysis, whilst the CRY2, PER1 (except dorsal fat) and PER2 (except hypothalamus) genes generally show negative log2(FC) values. Such result might be explained by the existence of a negative feedback loop between the ARNTL/NPAS2 and CRY/PER genes. Collectively, these results support that nutrition plays an important role in modulating the timing of porcine peripheral circadian clocks. Such regulation could be essential for coordinating the subsequent metabolic response to nutrient supply.